Endoscopic ultrasonography-guided hepaticogastrostomy as a bridge to the definitive biliary reconstruction in a pediatric patient with left hepatic duct disruption secondary to blunt liver trauma - Kaori Ito; Takao Itoi; Seisuke Sakamoto; Mureo Kasahara; Yasufumi Miyake; Tetsuya Sakamoto (Elsevier, 2020)
Case report: Endoscopic ultrasonography-guided hepaticogastrostomy (EUS-HGS) is a minimally invasive technique for biliary system drainage that is used in adult patients with biliary obstruction whose papilla of Vater cannot be accessed. We report a pediatric patient who developed complete obstruction of left hepatic duct associated with liver injury and underwent EUS-HGS as a bridge to the definitive biliary reconstruction. A 7-year-old boy sustained a liver injury (Grade IV) developed bile peritonitis post-traumatic day 17 and underwent perihepatic drainage followed by endoscopic retrograde cholangiopancreatography, which revealed persistent bile leakage from B8. The left biliary system was not visible. A 7-Fr plastic stent was placed into the right biliary system, but 1 week later the patient developed diffuse dilatation of the left biliary system due to complete obstruction of left hepatic duct. EUS-HGS was performed to drain the left biliary system. A dilated bile duct (B2) was accessed using a needle through the EUS probe. A 7-Fr plastic stent was placed into B2 over the guidewire. Eight months later, he underwent elective exploratory laparotomy and hepaticojejunostomy by pediatric hepatobiliary surgeons. Conclusion: Temporarily draining the biliary system by EUS-HGS is a viable option prior to definitive biliary reconstructive surgery.